The preventive Control of White Root Rot Disease in Small Holder Rubber Plantation Using Botanical, Biological and Chemical Agents - Joko Prasetyo; Titik Nur Aeny (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2013)
The preventive control of white root rot disease in small holder plantation using botanical, biological, and chemical agents. A field and laboratory experiment were conducted from June 2008 to December 2009 in Panumangan, Tulang Bawang - Lampung. The field experiment was intended to evaluate the effect of botanical plants (Alpinia galanga, Sansiviera auranthii, and Marantha arundinacea), biological agents (organic matter and Trichoderma spp.), and chemical agents (lime and natural sulphur) on the incidence of white root rot disease and population of some soil microbes. The laboratory experiment was conducted to observe the mechanism of botanical agents in controlling white root rot disease. In the field experiment, the treatments were applied in the experimental plot with cassava plant infection as the indicator. The variables examined were the incidence of white root rot and population of soil microbes. In the laboratory experiment, culture of R. microporus was grown in PDA containing root exudate of the antagonistic plant (botanical agent). The variable examined was colony diameter of R. microporus growing in the PDA plates. The results of the field experiment showed that planting of the botanical agents, and application of Trichoderma spp., as well as natural sulphur, decreased the incidence of white root rot disease. The effectiveness of M. arundinacea and Trichoderma spp. was comparable to natural sulphur. The laboratory experiment showed only root exudate of A. galanga and S. auranthii that were significantly inhibit the growth of R. microporus.